2020
DOI: 10.9734/ajarr/2020/v8i130189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilizer and Inter Row Spacing on Herbage Yield and Some Yield Components (Number of Leaves and Number of Tillers per Plant) of Rhodes Grass (Chloris gayana Tan) in the Dry Sub Humid Zone of Sokoto Nigeria

Abstract: A field experiment was conducted during the 2016 and 2017 rainy seasons at Centre for Agriculture and Pastoral Research (CAPAR) of the Usmanu Danfodiyo University Sokoto, Nigeria to study the effect of nitrogen fertilizer and inter-row spacing on herbage yield and some yield parameters of Rhodes grass. A factorial combination of five fertilizer levels (0, 100, 120, 140 and 160 kgNha-1) and three inter row spacing (30, 50 and 70 cm) were used, making fifteen treatments combinations, which were laid out in a RCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…A higher number of tillers is an important attribute of grasses as it increases all higher than our ndings for C. gayana. However our result was higher than the report ofDaba et al (2019) in Ethiopia, but within the range of 10 to 22 recorded byIsa et al (2020) in Nigeria. For U. ruziziensis, our data for the number of tillers per plant was higher than the result ofCheruiyot et al (2018) who reported between 6.3 to 17.3 in cultivars of Urochloa in Kenya, but lower than the ndings ofWassie et al (2018) who reported up to 36 for U. brizantha cultivars in Ethiopia.…”
contrasting
confidence: 81%
“…A higher number of tillers is an important attribute of grasses as it increases all higher than our ndings for C. gayana. However our result was higher than the report ofDaba et al (2019) in Ethiopia, but within the range of 10 to 22 recorded byIsa et al (2020) in Nigeria. For U. ruziziensis, our data for the number of tillers per plant was higher than the result ofCheruiyot et al (2018) who reported between 6.3 to 17.3 in cultivars of Urochloa in Kenya, but lower than the ndings ofWassie et al (2018) who reported up to 36 for U. brizantha cultivars in Ethiopia.…”
contrasting
confidence: 81%